The Principal’s Leadership Strategy in Improving the Quality of Learning at MTs Darul Falah Sumbergempol Tulungagung - Eko Sigit Purwanto (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
This study is motivated by the leadership of the principal at MTs Darul Falah Sumbergempol Tulungagung, who involves all school personnel in school activities. Although the principal’s tenure is relatively new, the principal has been able to implement continuous changes to advance the institution and improve the quality and services of the school. The research employed a qualitative approach. Data were collected through participant observation, in-depth interviews, and documentation. The data analysis techniques included (1) data reduction, (2) data display, and (3) conclusion drawing/verification. The results of this study indicate that: (1) The principal’s strategy in mobilizing subordinates to improve the quality of learning at MTs Darul Falah Sumbergempol Tulungagung is carried out by ensuring that teachers perform their duties professionally, participating directly in the preparation of lesson plans (RPP), selecting competent teachers to guide students in self-development activities, providing explanations and motivation to subordinates regarding the implementation of tasks in the madrasah, and giving instructions to enhance staff capabilities by forming well-organized teamwork. (2) The principal’s strategy in influencing subordinates to improve the quality of learning is implemented by enhancing personnel performance, providing rewards to subordinates, setting a good example, showing concern and attention, improving welfare, motivating subordinates, and supporting as well as appreciating their achievements. (3) The principal’s strategy in encouraging improvements in the quality of learning is carried out by inviting subordinates to enhance teachers’ competencies, motivating teachers to be productive and innovative, coordinating the outcomes of teachers’ work, consistently evaluating teachers’ activities, conducting official meetings, providing motivation during these meetings, and setting an example by arriving at school earlier than others.